Determinants of FDI in developed and developing countries: a dynamic panel analysis - Aminath, Hasima (2021)
FDI can be described as the inflow and outflow of capital between countries resulting from investment. Over the past few decades FDI has proved to be an important contributing factor towards economic growth and technological transfers. In a world that is increasingly relying on technology for everyday economic activities, such transfers and spill overs are extremely beneficial for its economic strength. Therefore, the objective of this paper is to explore the determinants of FDI in developing and developed countries through panel data analysis by applying both static and dynamic approach for a sample of 18 countries; of which 9 developed and 9 developing economies, for the past 15 years from 2004 to 2018. For static approach, Hausman (1978) test is used to explain whether or not fixed/random effect model can be applied while the outcomes of generalized moments of methods (GMM) indicate endogeneity and unobserved heterogeneity of sample. Findings of this paper imply that FDI determinants are different across countries. For developed countries, FDI is attracted towards favourable policies such as GDP growth, trade openness and freedom of business while FDI in developing countries leans more towards favourable economic determinants such as Gross Fixed Capital Formulation (GFCF), efficiency and trade openness. This shows that the outcomes are in line with past research findings and hence agrees with traditional FDI determinant theories. It is important to note that these findings are limited to 18 countries and for a period of only 15 years. However, this paper provides some recommendations as to where government policies could focus in order to attract FDI considering how developed the country is. This research also sheds light on the importance of skill development, training and education for developing countries in order to reap the maximum benefits from both vertical and horizontal capital flows.